TOC prediction and grading evaluation based on variable coefficient △logR method and its application for unconventional exploration targets in Songliao Basin - Yu, Zhanqing; Ma, Shizhong; Liu, Chao (Frontiers in Earth Science, 2023)
Aiming at the need of new exploration targets of shale reservoirs which are highly heterogeneous vertically and horizontally in songliao basin, we have improved the application of variable coefficient △logR technique combined with conventional geochemical data in TOC prediction and grading evaluation of lacustrine shale. The variable coefficient △logR model utilized the two of acoustic logging and resistivity logging curve and the variable scale coefficient (K) between them as well as another scale coefficient (A) between TOC and △logR to establish the prediction model of total organic carbon. A prediction model of total organic carbon was established for the well with TOC of core test, and was applied to other wells to verify the reliability of the model. The results show that the maximum prediction accuracy k value varies with well in Shuangcheng area, so it is necessary to determine the undetermined coefficient K according to a single well. TOC of shale is linearly correlated with △logR. The similar sedimentary facies and thermal evolution degree of shale make the A value having no big change from one well to another. The final result show that the average relative error of shale between prediction model and core test is 10.6% which verifies the accuracy of this method. On this basis, we establish shale grading evaluation criteria for the study area. In the establishment process, not only the relationship between TOC and S1, but also vitrinite reflectance (Ro) are considered. The shales in Shuangcheng area can be divided into three types (Class I: TOC>3.5% and Ro>0.9%; Class II: TOC 2%-3.5% and Ro>0.9; Class III: TOC<2% or Ro<0.9%), and achieved shale classification on the well profile with TOC and Ro which are easy to predict and reliable. According to the relationship between the thickness of shale of disparate classes and the total thickness of shale in different zones, the thickness of shale of disparate classes in each well is predicted. The application results of 11 prospecting wells in study area confirm that the variable coefficient △logR method can accurately predict TOC of lacustrine shale and guide the shale grading evaluation.